Beauty is in the eye of the beholder: The role of construal level in reducing the "beauty-is-good" bias contributing to food waste reduction- Abstract - Castagna, Ana Carina (2019)
Castagna, A. C., Pinto, D. C., & Barcellos, M. D. D. (2019). Beauty is in the eye of the beholder: The role of construal level in reducing the "beauty-is-good" bias contributing to food waste reduction- Abstract. In Proceedings of the European Marketing Academy, 48th (pp. 1-2). European Marketing Academy (EMAC). http://proceedings.emac-online.org/pdfs/A2019-8231.pdf